Fight‐flight or freeze‐hide? Personality and metabolic phenotype mediate physiological defence responses in flatfish. (16th May 2016) - Rupia, Emmanuel J.; Binning, Sandra A.; Roche, Dominique G.; Lu, Weiqun
Summary: Survival depends on appropriate behavioural and physiological responses to danger. In addition to active 'fight‐flight' defence responses, a passive 'freeze‐hide' response is adaptive in some contexts. However, the physiological mechanisms determining which individuals choose a given defence response remain poorly understood. We examined the relationships among personality, metabolic performance and physiological stress responses across an environmental gradient in the olive flounder, Paralichthys olivaceus . We employed four behavioural assays to document the existence of two distinct behavioural types ('bold' and 'shy') in this species. We found consistent metabolic differences between individuals of a given behavioural type across an environmental gradient: shy individuals had overall lower aerobic scope, maximum metabolic rate and standard metabolic rate than bold individuals in both high (25 ppt) and low (3 ppt) salinity. These behavioural and metabolic differences translated into divergent physiological responses during acute stress: shy individuals adopted a passive 'freeze‐hide' response by reducing their oxygen consumption rates (akin to shallow breathing) whereas bold individuals adopted an active 'fight‐flight' response by increasing their rates of respiration. These distinct defence strategies were repeatable within individuals between salinity treatments. Although it has been suggested theoretically, this is the first empirical evidence that the metabolic response to stressful situations differs between bold and shy individuals. Our results emphasize the importance of incorporating physiological measures to understand the mechanisms driving persistent inter‐individual differences in animals. Abstract : Animals have different strategies for dealing with danger, but the physiological mechanisms responsible for choosing an active vs. passive defense response are unclear. The authors show that the type (flee vs. freeze) rather than the magnitude of the behavioural and physiological response to a threat differs between bold and shy individuals.